Fukuoka City : Efficient Water Management - Kriss, Paul; Miki-Imoto, Haruka; Nishimaki, Hiroshi; Riku, Takashi (World Bank, Washington, DC, 2020)
This case study showcases examples where the “G20 Principles for Quality Infrastructure Investment (QII)” have been operationalized in Japan`s urban infrastructure projects. It highlights Fukuoka City, one of the most prominent cities in Japan today. It reviews the city’s efficient water management through Economic Efficiency and Infrastructure Governance, two of the six G20 Principles for QII. A key factor for the city’s success was adopting life-cycle costing as an underlying principle; the city upgraded its water distribution pipe network with polyethylene sleeves for life extension and went to great length for leakage reduction. As a recent effort, the city underwent procurement reforms to improve the technical quality of public works. The implications are expected to benefit policymakers and practitioners in developing countries.